2017
DOI: 10.4085/1062-6050-51.12.21
|View full text |Cite
|
Sign up to set email alerts
|

Concussion Baseline Testing: Preexisting Factors, Symptoms, and Neurocognitive Performance

Abstract: Main Outcome Measure(s): To determine neurocognitive functioning and total symptom score at baseline, ImPACT was administered. Outcomes were verbal memory, visual memory, visual motor speed, reaction time, and total symptom score. A self-report demographic section at the beginning of ImPACT was used to gather information concerning previous treatment for headaches, migraines, and psychiatric conditions; diagnosis of attention-deficit/hyperactivity disorder; and exposure to previous strenuous exercise. We condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 28 publications
5
45
4
Order By: Relevance
“…Our findings are inconsistent with those of Covassin et al 4 and Hall et al 11 in that we found that individuals who had engaged in self-reported strenuous exercise prior to ImPACT baseline test administration had significantly lower verbal memory and visual memory scores and significantly higher scores on reaction time, impulse control, and total symptoms. Covassin et al found a decrease in only verbal memory, and Hall et al found no significant difference in neurocognitive scores.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings are inconsistent with those of Covassin et al 4 and Hall et al 11 in that we found that individuals who had engaged in self-reported strenuous exercise prior to ImPACT baseline test administration had significantly lower verbal memory and visual memory scores and significantly higher scores on reaction time, impulse control, and total symptoms. Covassin et al found a decrease in only verbal memory, and Hall et al found no significant difference in neurocognitive scores.…”
Section: Discussioncontrasting
confidence: 99%
“…Such variation in type and amount of exercise may have caused the observed difference in results. One possible explanation for the difference in findings between the current study and Hall et al 11 is the number of covariates controlled. The current study accounted for the covariates of age, education level, concussion history, and hours of sleep prior to testing, while the study by Hall et al did not.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Prior studies assessing cognitive functioning before and after exercise have found mixed results regarding the effect of exercise. [25][26][27] We found that exercise did not have a clinically meaningful effect on EYE-SYNC ® goggles mean dynamic visual performance scores, as indicated by the small effect sizes observed in most of the pre-post practices measures. Despite a statistically significant difference in pre/post exercise scores, we found minimal changes in DVS measures pre-to-post practice, with absolute mean changes ranging from 0.02 (0.05) for horizontal gain to 0.1 (0.5) for SD tangential error.…”
Section: Discussionmentioning
confidence: 79%
“…Studies using the ImPACT test have shown female athletes in middle school, high school, and college exhibited a statistically significant greater aggregate symptom severity and longer reaction time than males [ 9 , 10 , 11 ] at baseline. A study conducted by Cottle and colleagues showed that female collegiate students performed better on ImPACT’s visual memory, visual motor speed, and reaction time than males [ 12 ]. However, no studies were found assessing sex differences using the new tool, ImPACT Pediatric, among 5–11-year-old children.…”
Section: Introductionmentioning
confidence: 99%